"Pamiętaj, abyś święcił dzień szabatu" (Wj 20,8; Pwt 5,12). Studium egzegetyczno-teologiczne - Filipiak, Marian (The Biblical Annals, 2017)
The sabbath is a typically Israeli holiday. There are no sufficient proofs that it has been adopted from other nations. It was either an old Israeli custom finally sanctioned by Moses, or Moses himself established it. Various definitions of the sabbath comprised in the traditions of the Pentateuch point to the fact, that the fundamental meaning of the sabbath was equal to stopping the work. The holiday of the seventh day was observed by the very fact of rest and in the epoch of ancient Israel it had nothig to do with a positive dipt of Jahwe. To the social motivation of the sabbath the religious m otivation was later joined, and with time it acquired the decisive role.